Sosialisasi Kenali & Cegah HIV/AIDS Bersama di SMK Negeri 1 Kota Bengkulu - Anggun seftiany; Susan Tina Wontu; Lovia Sadatun Hariani; Revani Hargianti; Hasana Putri; Habibi Ardiansyah; Ika Pasca Himawati; Rany Claudia (Jurnal Pengabdian Cendekia, 2026)
HIV/AIDS remains a serious threat among Indonesian adolescents due to poor health literacy, particularly in Bengkulu City with 102 new cases in 2025. This study aimed to enhance HIV/AIDS knowledge among students of SMK Negeri 1 Bengkulu City through educational outreach. Quantitative quasi-experimental pre-test post-test one-   group design was employed. Population comprised all grade 10-12 students (n=500), with purposive sample of 60 students. Instrument was 5-item multiple-choice questionnaire, analyzed using Wilcoxon Signed-Rank Test (SPSS 26, p<0.05). Results demonstrated significant knowledge improvement from pre-test mean 40.33 (SD=19.99) to post-test 81.50 (SD=12.19), p=0.000. Conclusion: The outreach effectively built understanding of HIV definition, transmission, prevention, and inclusive attitudes toward PLWHA, contributing to HIV spread control in Bengkulu.